2017
DOI: 10.1080/19325037.2017.1343161
|View full text |Cite
|
Sign up to set email alerts
|

The Motivational Impact of Wearable Healthy Lifestyle Technologies: A Self-determination Perspective on Fitbits With Adolescents

Abstract: Background: Considerable numbers of young people are not meeting physical activity guidelines. Wearable fitness devices can provide opportunities for physical activity promotion. Purpose: The aim of the study was to explore whether wearable healthy lifestyle technologies impacted on adolescents' (13-to 14-year-olds) motivation for physical activity. Methods: The study was a mixed method sequential design. Participants were 84 adolescents (44 girls, 40 boys) from 6 physical education classes. Pupils were issued… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
128
1
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 151 publications
(167 citation statements)
references
References 56 publications
11
128
1
3
Order By: Relevance
“…Further, while a non-commercial app resulted in weight reduction and improvements to motivation, other nonrandomized interventions report no significant differences in diet/nutrition and/or physical activity behaviours (Dute et al, 2016). In our own study, reductions in motivation were reported, alongside feelings of guilt and internal pressure (Kerner & Goodyear, 2017). Similarly, Depper and Howe's (2017) concluded that apps reinforced narrow understanding of health that was related to fitness and slenderness in adolescent girls.…”
mentioning
confidence: 77%
See 1 more Smart Citation
“…Further, while a non-commercial app resulted in weight reduction and improvements to motivation, other nonrandomized interventions report no significant differences in diet/nutrition and/or physical activity behaviours (Dute et al, 2016). In our own study, reductions in motivation were reported, alongside feelings of guilt and internal pressure (Kerner & Goodyear, 2017). Similarly, Depper and Howe's (2017) concluded that apps reinforced narrow understanding of health that was related to fitness and slenderness in adolescent girls.…”
mentioning
confidence: 77%
“…This data was, therefore, not included. For further information, please see Kerner and Goodyear (2017).…”
Section: Data Generationmentioning
confidence: 99%
“…In order to make the physical exercises an integral part of the graduate's life, it is necessary to form an understanding of the role of physical activity for selfimprovement and health during his studentship, as well as conscious motives for these exercises and the ability to carry out sports activities on a standalone basis [7,8,9,10]. To this end, the curriculum includes hours for lecture classes in the course of which students are taught theoretical and methodological material on the subject with the most complete amount of information about the physiological effects of systematic classes; how the motion loads are optimized depending on the physical condition of the trainee, his level of health, personal tasks and other factors; about the fundamental laws the implementation of which allows to properly plan the process of preparation to achieve the resultsvictories in competitions, body shaping, increasing efficiency and health.…”
Section: Resultsmentioning
confidence: 99%
“…Recent study concludes that activity tracker users feel unmotivated despite having an awareness of benefits of physical activity [27]. Users can become demotivated if they cannot meet their activity goals [28].…”
Section: Discussionmentioning
confidence: 99%